SPIRITUAL DEPICTION OF THE FEMALE IN THE WORK OF NURALI KABUL (Scientific journal of the Fergana State University, 2023)
The article tells about the qualities inherent in Uzbek women using the example of the image of Zulayho, the main character of the story "Hello, mountains", which belongs to the pen of Nurali Kabul, a talented writer of modern Uzbek literature. Also, through the image of the female psyche, the issue of how the negative impact of war on women's fate was illuminated by the writer was subjected to analysis.